2009
DOI: 10.1136/aim.2009.000703
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of Involuntary Movements in Cerebral Palsy with Acupuncture

Abstract: This case describes the treatment of severe involuntary movements in a 10-year-old boy suffering from cerebral palsy. Needling GB34 and ST36 bilaterally for 25 minutes resulted in immediate temporary cessation of involuntary extension contractions of the erector spinae muscles for the duration of the treatment, resulting in increased functionality in the patient. This response occurred regularly on repeated treatment, but was not maintained between treatments. Involuntary movements are a major disabling feat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0
1

Year Published

2010
2010
2019
2019

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 20 publications
0
4
0
1
Order By: Relevance
“…And accumulated clinical evidence suggests that acupuncture improved the life quality of CP children and promoted the progression in cognitive, neurobehavior, motor dysfunction, and linguistic retardation (Liu et al, 2010;Sun et al, 2004;Watson, 2009;Wong et al, 2006;Wu et al, 2008;Zou et al, 2013). However, the protective effects of acupuncture and the underlying mechanism have been not well illustrated.…”
Section: Introductionmentioning
confidence: 97%
“…And accumulated clinical evidence suggests that acupuncture improved the life quality of CP children and promoted the progression in cognitive, neurobehavior, motor dysfunction, and linguistic retardation (Liu et al, 2010;Sun et al, 2004;Watson, 2009;Wong et al, 2006;Wu et al, 2008;Zou et al, 2013). However, the protective effects of acupuncture and the underlying mechanism have been not well illustrated.…”
Section: Introductionmentioning
confidence: 97%
“…In this study, we selected ST36 and its sham point and used single and paired TMS to measure MEP, SICI, and LICI during acupuncture. ST36 is used to treat dyskinesia and may be related to the recovery of the motor cortex (Watson, ). In addition, neuroimaging findings have shown that acupuncture at ST36 is associated with the supplementary motor area (Mazoyer et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…ST36 is used to treat dyskinesia and may be related to the recovery of the motor cortex (Watson, 2009). In addition, neuroimaging findings have shown that acupuncture at ST36 is associated with the supplementary motor area (Mazoyer et al, 2001).…”
Section: Introductionmentioning
confidence: 99%
“…CP is one of the consequences of HIE that acupuncture might have some beneficial effects in children [45][46][47][48][49]. Clinical evidence showed that acupuncture therapy intervention could improve the quality of life and promote improvements in speech and language impairment, neural function, motor disability, and cognition [45,46,[50][51][52][53].…”
Section: Clinical Trialmentioning
confidence: 99%